2023
DOI: 10.4314/gjg.v15i2.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Non-Governmental Sector in Community Water, Sanitation and Hygiene Technologies and Services in North- Western Ghana

Francis Issahaku Malongza Bukari,
Raymond Aabeyir,
Adams Sulemana Achanso

Abstract: Despite the Sustainable Development Goals which have been adopted since September 2015, researchfindings on sectoral achievements of the gaols are inadequate. This study ascertained the approaches,effectiveness, implications and challenges of the Centre for Indigenous Knowledge and OrganisationalDevelopment as a Non-Governmental Organisation (NGO), in promoting access to water, sanitation andhygiene (WASH) through its water for resilience project in rural communities of the Lawra Municipalityand Nandom Distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Selection of relevant texts for literature from the internet was aided using the Boolean search terms. By this, combined keywords related to the specific research objectives, using AND, NOT and OR as operators were used in the online search to generate the required literature for further interpretation and synthesis (Bukari et al, 2023).Examples of search terms used in this study were the uses of groundwater, groundwater governance and management in the rural communities, accessibility of groundwater, affordability of groundwater, and livelihood effects of groundwater use. Both primary and secondary data sources were gathered and analysed based on these thematic areas or search terms woven around the research objectives.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Selection of relevant texts for literature from the internet was aided using the Boolean search terms. By this, combined keywords related to the specific research objectives, using AND, NOT and OR as operators were used in the online search to generate the required literature for further interpretation and synthesis (Bukari et al, 2023).Examples of search terms used in this study were the uses of groundwater, groundwater governance and management in the rural communities, accessibility of groundwater, affordability of groundwater, and livelihood effects of groundwater use. Both primary and secondary data sources were gathered and analysed based on these thematic areas or search terms woven around the research objectives.…”
Section: Methodsmentioning
confidence: 99%
“…Grigg (2016), also examined the social aspects of water management, but his focus was on collective action in water service management rather than groundwater issues. In Ghana, Bukari et al (2023) investigated water technologies in the Lawra Municipal and Nandom Districts of the Upper West Region of Ghana, but their study was not focused on groundwater, but rather general water, sanitation and hygiene technologies and the activities of the non-governmental sector in the provision of such infrastructure, which satisfies the 'enterprise' component of the definition of infrastructure provided by Beeferman and Wain (2019). Adank et al (2013) also investigated the status of rural water services in Ghana, and identified mechanised boreholes, hand pumps and dug wells as rural groundwater point source infrastructure.…”
Section: Background Of the Studymentioning
confidence: 99%
See 2 more Smart Citations